Low-cost high-capacity layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof
The Na0.67NixCuyZn0.03Mg0.05Mn0.92-x-yO2 layered sodium oxide battery positive electrode material prepared by sand milling spray method solves the problem of insufficient capacity of existing sodium ion battery positive electrode materials, achieves high capacity and low cost effects, and is suitable for large-scale energy storage applications.
Patent Information
- Application Number
- CN202510086364.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lack of suitable positive electrode materials with high capacity in existing sodium ion batteries limits its marketization process.
A low-cost, high-capacity layered sodium oxide battery cathode material is prepared by sand mill spraying method. The chemical formula is Na0.67NixCuyZn0.03Mg0.05Mn0.92-x-yO2. By controlling the Ni and Cu content and sintering conditions, the capacity and production efficiency of the material are improved.
The prepared sodium ion battery cathode material has high capacity and low cost, is suitable for large-scale energy storage devices, and the method used is suitable for mass production.
Smart Images

Figure CN119905573A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a low-cost and high-capacity layered oxide sodium ion battery positive electrode material, and a preparation method and application thereof. Background Art
[0002] With the increasing depletion of traditional fossil fuels such as coal and oil, and the resulting environmental problems such as increased greenhouse gas emissions and intensified air pollution, human society is facing tremendous pressure for energy transformation. This has prompted people to accelerate the development of new clean energy and new energy storage technologies to achieve sustainable development. Among the many energy storage technologies, lithium-ion batteries have occupied a large share in the market due to their significant characteristics such as high energy density, good cycle stability, and high charge and discharge efficiency. They are widely used in consumer electronics, electric vehicles, and energy storage systems. However, in recent years, with the continuous growth of global demand for lithium-ion batteries, the supply of key resources such as lithium and cobalt has become increasingly prominent, which has not only led to fluctuations in raw material prices, but also caused concerns about resource sustainability. This has forced people to actively develop alternatives to lithium-ion batteries to ensure the long-term and stable development of energy storage technology.
[0003] Among the many alternatives to lithium-ion batteries, sodium-ion batteries have the prospect of rapid commercialization due to their high abundance of sodium resources and similar working mechanisms to lithium-ion batteries. In addition, sodium-ion batteries are superior to lithium-ion batteries in terms of high and low temperature performance and safety performance, making sodium-ion batteries have more obvious advantages in the field of large-scale energy storage and are considered to be "the most promising next-generation energy storage device."
[0004] However, the lack of suitable cathode materials is still an important factor restricting the development of sodium-ion batteries and hindering their marketization. Layered transition metal oxides are a particularly important type of cathode material for sodium-ion batteries, but their capacity needs to be improved. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the object of the present invention is to provide a low-cost, high-capacity layered oxide sodium ion battery positive electrode material and a preparation method and application thereof, wherein the prepared sodium ion battery positive electrode material has a higher capacity.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] In the first aspect, the present invention first provides a low-cost and high-capacity layered oxide sodium ion battery positive electrode material, the chemical formula of which is Na 0.67 Ni x Cu y Zn 0.03 Mg 0.05 Mn0.92-x-y O2, where 0.05≤x<0.15, 0.05≤y≤0.1.
[0008] In a second aspect, the present invention also provides a method for preparing a low-cost and high-capacity layered oxide sodium ion battery positive electrode material, using a sand mill spray method, comprising the following steps:
[0009] S1, dissolving a sodium source compound, a nickel source compound, a copper source compound, a zinc source compound, a magnesium source compound and a manganese source compound in water according to a molar ratio to obtain a slurry, and performing sand milling to obtain a sand milled slurry;
[0010] S2, transferring the sand-milled slurry into a spray dryer for spray drying at high temperature with an evaporation rate of 5 L / h to obtain a spray-dried material;
[0011] S3, the spray-dried material is loaded into a sagger, and high-temperature sintering is performed in an air atmosphere at a temperature of 800-1000° C. for 10-20 hours, and the material is naturally cooled and air flow crushed to a particle size of 4-6 μm to obtain a positive electrode material for a sodium ion battery.
[0012] Further, the sodium source compound in S1 is selected from one or more of sodium carbonate, sodium hydroxide, sodium oxide, sodium acetate, sodium nitrate, sodium oxalate and sodium citrate; the nickel source compound is selected from one or more of nickel oxide, nickel acetate, nickel nitrate, nickel oxalate and nickel sulfate; the copper source compound is selected from one or more of copper oxide, copper acetate, copper nitrate, copper oxalate and copper sulfate; the zinc source compound is selected from one or more of zinc oxide, zinc acetate, zinc nitrate, zinc oxalate and zinc sulfate; the magnesium source compound is selected from one or more of magnesium oxide, magnesium acetate, magnesium nitrate, magnesium oxalate and magnesium sulfate; the manganese source compound is selected from one or more of manganese tetraoxide, manganese dioxide, manganese trioxide, manganese acetate, manganese nitrate, manganese oxalate and manganese sulfate.
[0013] Furthermore, the solid content of the slurry in S1 is maintained at 20-60%.
[0014] Furthermore, the sand grinding time in S1 is 5 h, and the grain size is ground to 1-3 μm.
[0015] Furthermore, the outlet temperature of the spray drying in S2 is 100-200°C.
[0016] Furthermore, the more optimal sintering temperature in S3 is 900-950°C and the time is 15h.
[0017] In a third aspect, the present invention also provides a low-cost, high-capacity layered oxide sodium ion battery positive electrode material for use in large-scale energy storage devices such as electric vehicles, solar power generation, wind power generation, smart grid peak regulation, distributed power stations or communication bases.
[0018] Furthermore, when used, the positive electrode material of the sodium ion battery needs to be first prepared into a positive electrode sheet of the sodium ion battery, and then assembled with a separator, an organic electrolyte and a negative electrode metal sodium into a sodium ion battery.
[0019] Furthermore, the positive electrode sheet of the sodium ion battery also includes a conductive additive, a binder and a solvent, the conductive additive is selected from one or more of Super-P, carbon black and Ketjen black; the binder is selected from one or more of polyvinylidene fluoride, polyacrylic acid, sodium carboxymethyl cellulose and sodium alginate; the solvent is selected from one of N-methylpyrrolidone or deionized water.
[0020] Furthermore, the separator of the sodium ion battery is preferably glass fiber; the organic electrolyte is a carbonate electrolyte with a concentration of 0.5-2M, preferably 1M; the solvent in the organic electrolyte is selected from at least one of diethyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate and fluorinated ethylene carbonate, preferably a mixed solvent of propylene carbonate and fluorinated ethylene carbonate; the solute in the organic electrolyte is selected from at least one of sodium perchlorate, sodium hexafluorophosphate, and sodium bis(trifluoromethylsulfonyl)imide, preferably sodium perchlorate.
[0021] Beneficial effects of the present invention:
[0022] (1) The chemical formula of the sodium ion battery positive electrode material prepared by the present invention is Na 0.67 Ni x Cu y Zn 0.03 Mg 0.05 Mn 0.92-x-y O2 (0.05≤x<0.15, 0.05≤y≤0.1), enriching the material system of sodium-ion batteries.
[0023] (2) The sodium ion battery positive electrode material Na prepared by the present invention 0.67 Ni x Cu y Zn 0.03 Mg 0.05 Mn 0.92-x-y O2 (0.05≤x<0.15, 0.05≤y≤0.1) has a low Ni content, which reduces the cost and has a higher capacity.
[0024] (3) The sodium ion battery positive electrode material Na prepared by the present invention 0.67 Ni x Cu y Zn 0.03 Mg 0.05 Mn 0.92-x-yThe method used for O2 (0.05≤x<0.15, 0.05≤y≤0.1) is the sanding spray method, which is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention will be further described below in conjunction with the accompanying drawings.
[0026] Figure 1 is a SEM image of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;
[0027] Figure 2 is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;
[0028] Figure 3 is a charge and discharge curve at a rate of 0.1C when the sodium ion battery positive electrode material prepared in Example 1 of the present invention is used in a sodium ion battery;
[0029] Figure 4 is the charge and discharge curve at 0.1C rate when the sodium ion battery positive electrode material prepared in Example 2 of the present invention is used in a sodium ion battery;
[0030] Figure 5 is the charge and discharge curve at 0.1C rate when the sodium ion battery positive electrode material prepared in Example 3 of the present invention is used in a sodium ion battery;
[0031] Figure 6 is the charge and discharge curve at 0.1C rate when the sodium ion battery positive electrode material prepared in Example 4 of the present invention is used in a sodium ion battery;
[0032] Figure 7 is the charge and discharge curve at 0.1C rate when the sodium ion battery positive electrode material prepared in Example 5 of the present invention is used in a sodium ion battery;
[0033] Figure 8 This is the charge and discharge curve at a rate of 0.1C when the sodium ion battery positive electrode material prepared in Example 6 of the present invention is used in a sodium ion battery. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a low-cost and high-capacity layered oxide sodium ion battery positive electrode material Na 0.67 Ni0.12 Cu 0.05 Zn 0.03 Mg 0.05 Mn 0.75 O2 was prepared by sand mill spray method, which included the following steps:
[0037] S1, dissolving sodium carbonate, nickel oxide, copper oxide, zinc oxide, magnesium oxide and manganese tetraoxide in water according to a molar ratio to obtain a slurry, maintaining the solid content of the slurry at 40%, and sand milling for 5 hours to a particle size of 1-3 μm to obtain a sand-milled slurry;
[0038] S2, transferring the sand-milled slurry into a spray dryer for spray drying, with the spray outlet temperature being 160°C and the evaporation rate being 5L / h to obtain a spray-dried material;
[0039] S3, the spray-dried material is loaded into a sagger, and sintered at high temperature in an air atmosphere at 900°C for 15 hours, cooled naturally, and air flow crushed to a particle size of 4-6 μm to obtain the sodium ion battery positive electrode material Na 0.6 7Ni 0.12 Cu 0.05 Zn 0.03 Mg 0.05 Mn 0.75 O2.
[0040] The above-mentioned sodium ion battery positive electrode material, conductive additive (Super-P) and binder (polyvinylidene fluoride) are mixed in a mass ratio of 8:1:1, and a solvent (N-methylpyrrolidone) is added. After pulping, coating, drying and other steps, a sodium ion battery positive electrode sheet is obtained.
[0041] The above-mentioned sodium ion battery positive electrode sheet and the metallic sodium negative electrode are assembled into a sodium ion battery, GF / F is a battery separator, and the electrolyte is a carbonate electrolyte (1M NaClO4 PC solution contains 5 vol% FEC).
[0042] Figure 1 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 1, showing that the material has a disc-like morphology and the particle size is 4-6 μm;
[0043] Figure 2 This is the XRD diagram of the sodium ion battery positive electrode material prepared in Example 1, which shows that the synthesized material has good crystallinity;
[0044] Figure 3 This is the charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 1 at a rate of 0.1C when used in a sodium ion battery; it can be seen that the sodium ion battery positive electrode material has a higher specific capacity of 123.4mAh / g when used in a sodium ion battery, and has a higher average operating voltage of 3.54V.
[0045] Example 2
[0046] This embodiment provides a low-cost and high-capacity layered oxide sodium ion battery positive electrode material Na 0.67 Ni 0.14 Cu 0.08 Zn 0.03 Mg 0.05 Mn 0.7 O2 was prepared by sand mill spray method, which included the following steps:
[0047] S1, dissolving sodium carbonate, nickel oxide, copper oxide, zinc oxide, magnesium oxide and manganese tetraoxide in water according to a molar ratio to obtain a slurry, maintaining the solid content of the slurry at 40%, and sand milling for 5 hours to a particle size of 1-3 μm to obtain a sand-milled slurry;
[0048] S2, transferring the sand-milled slurry into a spray dryer for spray drying, with the spray outlet temperature being 160°C and the evaporation rate being 5L / h to obtain a spray-dried material;
[0049] S3, the spray-dried material is loaded into a sagger, and sintered at high temperature in an air atmosphere at 900°C for 15 hours, cooled naturally, and air flow crushed to a particle size of 4-6 μm to obtain the sodium ion battery positive electrode material Na 0.6 7Ni 0.14 Cu 0.08 Zn 0.03 Mg 0.05 Mn 0.7 O2.
[0050] The above-mentioned sodium ion battery positive electrode material, conductive additive (Super-P) and binder (polyvinylidene fluoride) are mixed in a mass ratio of 8:1:1, and a solvent (N-methylpyrrolidone) is added. After pulping, coating, drying and other steps, a sodium ion battery positive electrode sheet is obtained.
[0051] The above-mentioned sodium ion battery positive electrode sheet and the metallic sodium negative electrode are assembled into a sodium ion battery, GF / F is a battery separator, and the electrolyte is a carbonate electrolyte (1M NaClO4 PC solution contains 5 vol% FEC).
[0052] Figure 4 This is the charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 2 at a rate of 0.1C when used in a sodium ion battery; it can be seen that the sodium ion battery positive electrode material has a higher specific capacity of 120.7 mAh / g when used in a sodium ion battery, and has a higher average operating voltage of 3.51V.
[0053] Example 3
[0054] This embodiment provides a low-cost and high-capacity layered oxide sodium ion battery positive electrode material Na 0.67 Ni 0.1 Cu 0.0 8Zn 0.03 Mg 0.05 Mn 0.74 O2 was prepared by sand mill spray method, which included the following steps:
[0055] S1, dissolving sodium carbonate, nickel oxide, copper oxide, zinc oxide, magnesium oxide and manganese tetraoxide in water according to a molar ratio to obtain a slurry, maintaining the solid content of the slurry at 40%, and sand milling for 5 hours to a particle size of 1-3 μm to obtain a sand-milled slurry;
[0056] S2, transferring the sand-milled slurry into a spray dryer for spray drying, with the spray outlet temperature being 160°C and the evaporation rate being 5L / h to obtain a spray-dried material;
[0057] S3, the spray-dried material is loaded into a sagger, and sintered at high temperature in an air atmosphere at 900°C for 15 hours, cooled naturally, and air flow crushed to a particle size of 4-6 μm to obtain the sodium ion battery positive electrode material Na 0.6 7Ni 0.1 Cu 0.08 Zn 0.03 Mg 0.05 Mn 0.74 O2.
[0058] The above-mentioned sodium ion battery positive electrode material, conductive additive (Super-P) and binder (polyvinylidene fluoride) are mixed in a mass ratio of 8:1:1, and a solvent (N-methylpyrrolidone) is added. After pulping, coating, drying and other steps, a sodium ion battery positive electrode sheet is obtained.
[0059] The above-mentioned sodium ion battery positive electrode sheet and the metallic sodium negative electrode are assembled into a sodium ion battery, GF / F is a battery separator, and the electrolyte is a carbonate electrolyte (1M NaClO4 PC solution contains 5 vol% FEC).
[0060] Figure 5 This is the charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 3 at a rate of 0.1C when used in a sodium ion battery; it can be seen that the sodium ion battery positive electrode material has a higher specific capacity of 120.3mAh / g when used in a sodium ion battery, and has a higher average operating voltage of 3.51V.
[0061] Example 4
[0062] This embodiment provides a low-cost and high-capacity layered oxide sodium ion battery positive electrode material Na 0.67 Ni 0.08 Cu0.08 Zn 0.03 Mg 0.05 Mn 0.76 O2 was prepared by sand mill spray method, which included the following steps:
[0063] S1, dissolving sodium carbonate, nickel oxide, copper oxide, zinc oxide, magnesium oxide and manganese tetraoxide in water according to a molar ratio to obtain a slurry, maintaining the solid content of the slurry at 40%, and sand milling for 5 hours to a particle size of 1-3 μm to obtain a sand-milled slurry;
[0064] S2, transferring the sand-milled slurry into a spray dryer for spray drying, with the spray outlet temperature being 160°C and the evaporation rate being 5L / h to obtain a spray-dried material;
[0065] S3, the spray-dried material is loaded into a sagger, and sintered at high temperature in an air atmosphere at 900°C for 15 hours, cooled naturally, and air flow crushed to a particle size of 4-6 μm to obtain the sodium ion battery positive electrode material Na 0.6 7Ni 0.08 Cu 0.08 Zn 0.03 Mg 0.05 Mn 0.76 O2.
[0066] The above-mentioned sodium ion battery positive electrode material, conductive additive (Super-P) and binder (polyvinylidene fluoride) are mixed in a mass ratio of 8:1:1, and a solvent (N-methylpyrrolidone) is added. After pulping, coating, drying and other steps, a sodium ion battery positive electrode sheet is obtained.
[0067] The above-mentioned sodium ion battery positive electrode sheet and the metallic sodium negative electrode are assembled into a sodium ion battery, GF / F is a battery separator, and the electrolyte is a carbonate electrolyte (1M NaClO4 PC solution contains 5 vol% FEC).
[0068] Figure 6 This is the charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 4 at a rate of 0.1C when used in a sodium ion battery; it can be seen that the sodium ion battery positive electrode material has a higher specific capacity of 120.1mAh / g when used in a sodium ion battery, and has a higher average operating voltage of 3.55V.
[0069] Example 5
[0070] This embodiment provides a low-cost and high-capacity layered oxide sodium ion battery positive electrode material Na 0.67 Ni 0.06 Cu 0.08 Zn 0.03 Mg 0.05 Mn 0.78O2 was prepared by sand mill spray method, which included the following steps:
[0071] S1, dissolving sodium carbonate, nickel oxide, copper oxide, zinc oxide, magnesium oxide and manganese tetraoxide in water according to a molar ratio to obtain a slurry, maintaining the solid content of the slurry at 40%, and sand milling for 5 hours to a particle size of 1-3 μm to obtain a sand-milled slurry;
[0072] S2, transferring the sand-milled slurry into a spray dryer for spray drying, with the spray outlet temperature being 160°C and the evaporation rate being 5L / h to obtain a spray-dried material;
[0073] S3, the spray-dried material is loaded into a sagger, and sintered at high temperature in an air atmosphere at 900°C for 15 hours, cooled naturally, and air flow crushed to a particle size of 4-6 μm to obtain the sodium ion battery positive electrode material Na 0.6 7Ni 0.06 Cu 0.08 Zn 0.03 Mg 0.05 Mn 0.78 O2.
[0074] The above-mentioned sodium ion battery positive electrode material, conductive additive (Super-P) and binder (polyvinylidene fluoride) are mixed in a mass ratio of 8:1:1, and a solvent (N-methylpyrrolidone) is added. After pulping, coating, drying and other steps, a sodium ion battery positive electrode sheet is obtained.
[0075] The above-mentioned sodium ion battery positive electrode sheet and the metallic sodium negative electrode are assembled into a sodium ion battery, GF / F is a battery separator, and the electrolyte is a carbonate electrolyte (1M NaClO4 PC solution contains 5 vol% FEC).
[0076] Figure 7 This is the charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 5 at a rate of 0.1C when used in a sodium ion battery; it can be seen that the sodium ion battery positive electrode material has a higher specific capacity of 119.4mAh / g when used in a sodium ion battery, and has a higher average operating voltage of 3.51V.
[0077] Example 6
[0078] This embodiment provides a low-cost and high-capacity layered oxide sodium ion battery positive electrode material Na 0.67 Ni 0.13 Cu 0. 1Zn 0.03 Mg 0.05 Mn 0.69 O2 was prepared by sand mill spray method, which included the following steps:
[0079] S1, dissolving sodium carbonate, nickel oxide, copper oxide, zinc oxide, magnesium oxide and manganese tetraoxide in water according to a molar ratio to obtain a slurry, maintaining the solid content of the slurry at 40%, and sand milling for 5 hours to a particle size of 1-3 μm to obtain a sand-milled slurry;
[0080] S2, transferring the sand-milled slurry into a spray dryer for spray drying, with the spray outlet temperature being 160°C and the evaporation rate being 5L / h to obtain a spray-dried material;
[0081] S3, the spray-dried material is loaded into a sagger, and sintered at high temperature in an air atmosphere at 900°C for 15 hours, cooled naturally, and air flow crushed to a particle size of 4-6 μm to obtain the sodium ion battery positive electrode material Na 0.6 7Ni 0.13 Cu 0.1 Zn 0.03 Mg 0.05 Mn 0.69 O2.
[0082] The above-mentioned sodium ion battery positive electrode material, conductive additive (Super-P) and binder (polyvinylidene fluoride) are mixed in a mass ratio of 8:1:1, and a solvent (N-methylpyrrolidone) is added. After pulping, coating, drying and other steps, a sodium ion battery positive electrode sheet is obtained.
[0083] The above-mentioned sodium ion battery positive electrode sheet and the metallic sodium negative electrode are assembled into a sodium ion battery, GF / F is a battery separator, and the electrolyte is a carbonate electrolyte (1M NaClO4 PC solution contains 5 vol% FEC).
[0084] Figure 8 This is the charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 6 at a rate of 0.1C when used in a sodium ion battery; it can be seen that the sodium ion battery positive electrode material has a higher specific capacity of 122.8mAh / g when used in a sodium ion battery, and has a higher average operating voltage of 3.52V.
[0085] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0086] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low-cost, high-capacity layered oxide sodium ion battery positive electrode material, characterized in that: The chemical formula is Na 0.67 Ni x Cu y Zn 0.03 Mg 0.05 Mn 0.92-x-y O2, where 0.05≤x<0.15, 0.05≤y≤0.
1.
2. The method for preparing a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 1, characterized in that: The sanding spray method includes the following steps: S1, dissolving a sodium source compound, a nickel source compound, a copper source compound, a zinc source compound, a magnesium source compound and a manganese source compound in water according to a molar ratio to obtain a slurry, and performing sand milling to obtain a sand milled slurry; S2, transferring the sand-milled slurry into a spray dryer for spray drying at high temperature with an evaporation rate of 5 L / h to obtain a spray-dried material; S3, the spray-dried material is loaded into a sagger, and high-temperature sintering is performed in an air atmosphere at a temperature of 800-1000° C. for 10-20 hours, and the material is naturally cooled and air flow crushed to a particle size of 4-6 μm to obtain a positive electrode material for a sodium ion battery.
3. The method for preparing a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: The sodium source compound in S1 is selected from one or more of sodium carbonate, sodium hydroxide, sodium oxide, sodium acetate, sodium nitrate, sodium oxalate and sodium citrate; the nickel source compound is selected from one or more of nickel oxide, nickel acetate, nickel nitrate, nickel oxalate and nickel sulfate; the copper source compound is selected from one or more of copper oxide, copper acetate, copper nitrate, copper oxalate and copper sulfate; the zinc source compound is selected from one or more of zinc oxide, zinc acetate, zinc nitrate, zinc oxalate and zinc sulfate; the magnesium source compound is selected from one or more of magnesium oxide, magnesium acetate, magnesium nitrate, magnesium oxalate and magnesium sulfate; the manganese source compound is selected from one or more of manganese tetraoxide, manganese dioxide, manganese trioxide, manganese acetate, manganese nitrate, manganese oxalate and manganese sulfate.
4. The method for preparing a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: The solid content of the slurry in S1 was maintained at 20-60%.
5. The method for preparing a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: The sand grinding time in S1 is 5 h, and the grain size is 1-3 μm.
6. The method for preparing a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: The outlet temperature of the spray drying in S2 is 100-200°C.
7. The method for preparing a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: More preferably, the sintering temperature in S3 is 900-950°C and the sintering time is 15h.
8. The use of a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 1, characterized in that: The prepared sodium ion batteries are used in large-scale energy storage devices such as electric vehicles, solar power generation, wind power generation, smart grid peak regulation, distributed power stations or communication bases.
9. The use of a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 8, characterized in that: The sodium ion battery comprises a sodium ion battery positive electrode sheet, a conductive additive, a binder and a solvent.
10. The use of a low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 9, characterized in that: The sodium ion battery positive electrode sheet comprises the low-cost and high-capacity layered oxide sodium ion battery positive electrode material according to claim 1, a conductive additive, a binder and a solvent.
Citation Information
Patent Citations
Five-membered layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof
CN114927663A
Cu, Zn and Mg co-doped layered oxide sodium ion battery positive electrode material as well as preparation method and application thereof
CN115224254A
Layered oxide positive electrode material of sodium ion battery and preparation method of layered oxide positive electrode material
CN117393691A
Manganese-based sodium ion battery positive electrode material and preparation method thereof, positive electrode plate and sodium ion secondary battery
CN118763214A
Positive electrode active material and preparation method therefor, positive electrode sheet, and sodium-ion battery
WO2025007779A1